Ответы 1

  • \dfrac{3\ \text{lg}\ 2 - \text{lg} \ 24}{\text{lg} \ 3 + \text{lg} \ 27} = \dfrac{\text{lg}\ 2^{3} - \text{lg} \ 24}{\text{lg} \ 3 + \text{lg} \ 27} = \dfrac{\text{lg}\ 8 - \text{lg} \ 24}{\text{lg} \ 3 + \text{lg} \ 27} = \dfrac{\text{lg} \ \dfrac{8}{24}}{\text{lg} \ 3 \ \cdotp 27} = \dfrac{\text{lg}\ \dfrac{1}{3}}{\text{lg} \ 81} =\\\\ = \dfrac{\text{lg} \ 3^{-1}}{\text{lg} \ 3^{4}} = \dfrac{-\text{lg}\ 3}{4\ \text{lg} \ 3} = -\dfrac{1}{4}

  • Добавить свой ответ

Войти через Google

или

Забыли пароль?

У меня нет аккаунта, я хочу Зарегистрироваться

How much to ban the user?
1 hour 1 day 100 years